One-Step Regioselective Synthesis of Benzofurans from Phenols and α-Haloketones - Bingqiao Wang; Qiu Zhang; Juan Luo; Zongjie Gan; Wengao Jiang; Qiang Tang (Molecules, 2019)
Reported here is the direct synthesis of naphthofurans and benzofurans from readily available phenols and α-haloketones promoted by titanium tetrachloride which combines Friedel−Crafts-like alkylation and intramolecular cyclodehydration into one step. This simple protocol allows for the formation of a variety of high value naphthofurans and benzofurans within which a series of cyclic and acyclic groups are readily incorporated. This process demonstrates the advantages of high levels of regioselectivity, broad substrate scope, and moderate to excellent yields.